The Influence of Teaching Competence, Learning Motivation, and Learning Environment on Students’ Academic Achievement - Amaliah; Ibnu Muarif; Andriani Sariwardani; Muhammad Rusdi (Malaqbi Publisher, 2026)
This study examines the influence of teaching competence, learning motivation, and learning environment on students’ academic achievement. Using a quantitative explanatory research design, data were collected from 250 students through structured questionnaires and academic performance records. The data were analyzed using Structural Equation Modeling (SEM) to examine both direct and indirect relationships among variables. The results indicate that teaching competence, learning motivation, and learning environment significantly and positively affect students’ academic achievement. Among these variables, learning motivation was identified as the strongest predictor of academic performance. Furthermore, teaching competence and learning environment were found to significantly influence learning motivation, which in turn mediates their effects on academic achievement. The model explains 62% of the variance in academic achievement, demonstrating strong explanatory power. These findings highlight the importance of enhancing teacher competence, fostering student motivation, and creating supportive learning environments to improve educational outcomes. The study provides practical implications for educators, school administrators, and policymakers in designing strategies that promote academic excellence.